Perlindungan Hukum terhadap Game DreadOut dari Pembajakan di Situs Ilegal menurut Undang-Undang Hak Cipta - Ahnaf Nur Fauzan Romadhon; Ai Nazwa Nurbayati; Darmana Aries Setiawan; Farrel Ar Rasyid; Enjang Rohiman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid development of digital technology has driven the advancement of the gaming industry in Indonesia, including the emergence of local games such as DreadOut by Digital Happiness, which has gained international recognition. However, this success is accompanied by serious challenges in the form of piracy through illegal websites that harm copyright holders. This study aims to analyze the legal protection of the game DreadOut against piracy practices based on Law Number 28 of 2014 concerning Copyright. The method used is a normative juridical approach through statutory analysis and literature study. The findings show that DreadOut is a copyrighted work categorized as a video game and is legally protected. Nevertheless, law enforcement against piracy still faces various obstacles, such as the complaint-based offense system, low public awareness, and the ease of access to piracy sites. Therefore, stronger inter-agency cooperation, policy reforms to shift complaint-based offenses into ordinary offenses, and public education to increase respect for intellectual property rights are needed. Effective legal protection will support the growth of the local gaming industry and ensure the sustainability of Indonesian creative works in the digital era.